Diet\'s protein supplementation and Haemonchus contortus infection relation to the homeostasis, ovarian gene expression and histology of peripubertal ewes - Henriques, Paula Suarez (2021)
In ewes, the management of nutrition can be an efficient management tool to improve ovarian performance. Nutrients after being absorbed are transported by circulating blood to all tissues in the body. The ewe lamb nutritional and physiological state may interfere with the ovarian environment and fertility. A deficiency of protein in the blood caused by an Haemonchus contortus abomasal infection is detrimental to the organism\'s development during puberty, causing an undesirable delay in puberty manifestation. Pubertal delay leads to economic losses in sheep breeding economic systems. The infection demands a higher protein intake to repair the damage caused by the parasite in sheep\'s tissues, replenish the blood losses, and build the host\'s immune response. The immune response to H.contortus s improves with supplementation of protein in the sheep\'s diet. H.Contortus become resistant to anthelminthic therapy shortly after they are exposed to a new treatment.Moreover, there is the possibility of contamination by anthelmintic drugs in ovine products, possibly affecting human health and the environment. This study\'s objective was to evaluate if ovarian and clinical parameters can be incremented in peripubertal infected animals through more sustainable management than anthelmintic usage. We used a 2 x 2 factorial model where eighteen Santa Inês ewe lambs (Ovis aries) between 6 - 7 months old - born to the same ram - were fed with one of the two dietetic\'s protein levels (12% or 19%). After 35 days of being fed this diet, they were infected or not with 10,000 Haemonchus contortus L3 larvae. We assessed AMH plasma levels with an ELISA test and blood\'s cells and biochemical parameters during the experimental period at four different times. Following 42 days of infection and 77 days of the diet, the lambs had their left ovaries removed, and we examined ovarian morphometrics through histological analysis. The groups Supplemented Protein Infected(n=5), Control Protein Infected(n=5), Supplemented Protein Not Infected (n=4) and Control Protein Not Infected (n=4) did not differ in their bodyweight gain.In the analysis of plasma protein related to diet and infection in factorial ANOVA, the diet\'s protein level was significant (p=0.02). Primordial follicle size varied significantly with the interaction diet*infection (p<0.05) and oocyte size varied significantly with the level of protein in the diet (p=0.047). We created an explanatory linear mixed model to evaluate how diet, infection, and physiological parameters influenced the primordial follicle and oocyte size. Because the circulating nutrients reaching the ovary can change its gene expression, we decided to assess its gene expression. Ovarian follicle growth activation is an essential feature controlling female reproductive potential. We aimed to determine if supplementing protein in infected animals\' diet would impact the ovarian environment leading to timely ovarian follicle activation. After 77 days on this diet and 42 days of infection, we extracted RNA from their left ovaries and sequenced it to accomplish this goal. We found that protein supplementation in infected animals led to an up-regulation of genes and biological processes linked to meiotic activation in pre-ovulatory follicles and primordial follicle activation, among other processes. The supplemented not infected animals also up-regulated genes and processes linked to meiosis and other processes such as circadian behaviour. The animals that were not supplemented had these same processes down-regulated while they up-regulated processes related to tissue morphogenesis, inflammation and immune response. We concluded that serum AMH, blood cells and biochemical parameters, diet and infection influenced oocyte size and primordial follicle size in peripubertal ewes. Furthermore, diet\'s protein supplementation of peripubertal infected animals allowed them to express genes related to a more mature ovarian follicle stage than their half-sisters infected and not supplemented with protein. The supplementation of protein in not infected ewe lambs also led to up-regulation of genes and meiotic activation processes. In contrast, their half-sisters with control level of protein did not up-regulate these genes.